ASSESSMENT OF CADMIUM (Cd) CONTAMINATION IN MUD CRAB (Scylla spp.) AND SEDIMENT FROM SEGARA ANAKAN LAGOON, CILACAP, INDONESIA - Feri Susanto; Nuning Vita Hidayati; Agung Dhamar Syakti (Journal Omni-Akuatika, 2014)
The study aimes to examine the accumulation level of selected heavy metal Cd in various of common mud crab (Scylla spp.) samples from Segara Anakan Lagoon-Cilacap. Mangrove crab and sediment samples were taken from Segara Anakan (108046’–109005’E; 7034’–7048’S) and were analyzed using Atomic Absorption Spectrophotometer (AAS). The Cd extent in Scylla spp. varied from 0.084 - 0.273 ppm which still below the European Commission (2006) threshold value (0.5 ppm). On the other hand Cd concentration in sediment for most stations value (0.625 - 1.635 ppm) have exceeded the Interim marine sediment quality guidelines (ISQGs value; 0.7 ppm) except for station 2 and 4. Concerning the sediment, to interpret and assess the contamination status four indices were used, namely Contamination Factor (CF), Enrichment Factor (EF), Pollution Load Index (PLI), and Geoaccumulation Index (Igeo). The results show the Segara Anakan sediment value for CF varied 3.125 - 8.175, EF was 50.481, PLI was 5.381 and Igeo varied 0.319 - 0.736. The finding result shows the Segara Anakan sediment could be considered as moderately polluted.Keywords: cadmium, contamination, scylla, sediment.